Scheduling Irrigation Water Requirements of Bermuda grass (Cynodon dactylon) at King Saud University - SAEED, MOHAMMED ABDO (Journal of natural sciences, life and applied sciences, 2018)
In this study, scheduling the irrigation water requirements of Bermuda grass (Cynodon dactylon) has been determined at King Saud University. Soil and water samples from the study are analyzed to explore the properties of soil and water salinity respectively. The analysis of meteorological data indicates high and low reference evapotranspiration in July and January, respectively. The irrigation frequency in the study area differs from two days in April, May, June, July, August and September to six days in January. The irrigation requirements per the one period reaches to 19.33 mm.
Keywords: irrigation scheduling; reference evapotranspiration; water salinity; King Saud University